A multi-class SVM classifier ensemble for automatic hand washing quality assessment - Lacey, Gerard; LLorca, D.F.; Vilarino, F.; Zhou, Z. (My University, 2007)
Hand washing is a critical activity in preventing the spread of infection in health-care environments. Several guidelines recommended a hand washing protocol consisting of six steps that ensure that all areas of the hands are thoroughly cleaned. In this paper, we describe a novel approach that uses a computer vision system to monitor the user’s hands motions in order to ensure that the hand washing guidelines are followed. This work presents two main contributions: a description of a system which delivers robust segmentation of the hands using a combination of colour and motion analysis, and the implementation of a multi-class classification of the hand gestures using a SVM ensemble. The system performance is analysed and compared with human performance, showing an accuracy close to that of human experts.
British Machine Vision Conference
Keywords: Handwashing; Hand hygiene; Computer vision